2018
DOI: 10.1111/jnc.14476
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte truncated tropomyosin receptor kinase B mediates brain‐derived neurotrophic factor anti‐apoptotic effect leading to neuroprotection

Abstract: Open Science: This manuscript was awarded with the Open Materials Badge. For more information see: https://cos.io/our-services/open-science-badges/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 72 publications
(168 reference statements)
4
36
0
Order By: Relevance
“…Given that γ‐GCL activity is regulated at multiple levels, it is possible that PA affects transcriptional activity, whereas NDP‐MSH induces post‐transcriptional changes. Moreover, we recently reported that BDNF induces GSH synthesis in astrocytes and, in the present study, we show that NDP‐MSH prevented the reduction in BDNF expression induced by PA, suggesting that BDNF could be a mediator of NDP‐MSH antioxidant effect in astrocytes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Given that γ‐GCL activity is regulated at multiple levels, it is possible that PA affects transcriptional activity, whereas NDP‐MSH induces post‐transcriptional changes. Moreover, we recently reported that BDNF induces GSH synthesis in astrocytes and, in the present study, we show that NDP‐MSH prevented the reduction in BDNF expression induced by PA, suggesting that BDNF could be a mediator of NDP‐MSH antioxidant effect in astrocytes.…”
Section: Discussionsupporting
confidence: 76%
“…Intracellular ROS levels were detected using 2′‐7′‐dichlorofluorescein diacetate (DCFH‐DA) which, when hydrolysed within the cell, is oxidised to fluorescent dichlorofluorescein, as described by Saba et al . Cells were seeded onto 96‐well plates at a density of 3 × 10 4 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the role of BDNF in astrocytes. A previous study reported that BDNF delivery stimulated astrocytes to release neuroprotective factors, contributing to neuronal survival in the CNS (Saba et al, ), and the production of these neurotrophic factors was attenuated in GFAP‐specific TrkB knockout mice (Harada et al, ), indicating that the induction of neurotrophic factors in astrocytes could be triggered by activation of the BDNF/TrkB signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the effect of surgical incision-induced nociception on BDNF signaling pathway activation, ANA-12 was used to block the combination of BDNF and TrkB. 26 ANA-12 attenuated the increase in pTrkB and improvement in fear learning ability induced by surgical stimuli blockade. These data suggested that plantar incision-induced nociception decreased fear learning function by inhibiting the BDNF signaling pathway.…”
Section: Discussionmentioning
confidence: 99%